What Kind of Lithuania are We Fighting for When We Fight for the Lithuanian Freedom Fighters’ Memorial? - Statulevičiūtė-Kaučikienė, Rūta (Politologija, 2022)
Efforts to build a memorial to Lithuanian freedom fighters in Lukiškės Square in Vilnius have been fruitless for the third decade. During this period, as many as four competitions for artistic ideas were organized, but due to the dissatisfaction of various groups in society, no project was implemented in the square. The article analyzes the 2012-2020 period, which is framed by two state-organized competitions. Applying Ernesto Laclau and Chantal Mouffe’s discourse theory, it is aimed to open the very core of the conflict and to explain how and what historical memories of the Lithuanian freedom fighters are articulated by competing discourses consisting of linguistic and non-linguistic practices. Statements of politicians, cultural professionals, and the public in the national media and their modus operandi allow to identify opposite concepts of freedom, state, freedom fighters, monument, and its functions, and to single out the essential trophy of the competing discourses, an idea on which the public sharply disagrees.